Метод структурно-параметрического синтеза беспроводной сети доступа с использованием технологии Radio over Fiber - Переверзев, А. А.; Агеев, Д. В. (ХНУРЕ, 2013)
Radio access network over fiber technology combines both wireless and fiber-optic technology. The advantages of this technology are low attenuation, bigger network bandwidth, easy installation and management, reduced power consumption, multiservice, dynamic allocation of resources. The article is devoted to solving the problem of wireless access network design, which is based on usage on distribution network level radio over fiber (RoF) technology. Features of this method is its complexity. This method solves the problem as a design Wireless network as the synthesis of the distribution network. To solve the problem made it decomposed into three subtasks: frequency-territorial planning a wireless network, the synthesis of the distribution network topology, routing and wavelengths assignment they. Paid attention to the fact that routing and wavelength assigning necessary to consider the phenomenon of four-wave mixing, which has a significant impact on the probability of bit errors in data traffic on the network. Therefore, the proposed solution method is a modification of a previously known method and takes into account the phenomenon of four-wave mixing.
Keywords: RoF; BCO-RWA; световой путь; явление четырехволнового смешивания; WDM; безпроводная сеть; топология